2012
DOI: 10.1017/s000711451200342x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and immunomodulatory effects of tributyrin supplementation on experimental colitis

Abstract: Tributyrin (TBT) is a TAG composed of three butyric acids that has beneficial effects on ulcerative colitis due to its trophic, anti-inflammatory, pro-apoptotic and anti-carcinogenic properties. The goal of the present study was to evaluate the efficacy and mechanisms of action of TBT supplementation in the prevention of mucosal damage in experimental colitis. Mice received either a control diet or a TBT-supplemented diet for 15 d. Colitis was induced by dextran sodium sulphate administration during the last 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 52 publications
8
36
0
1
Order By: Relevance
“…These results further suggest that administration of butyrate (e.g. tributyrin) and/or promoting butyrate-producing bacteria may be of therapeutic benefit (55). …”
Section: Discussionmentioning
confidence: 87%
“…These results further suggest that administration of butyrate (e.g. tributyrin) and/or promoting butyrate-producing bacteria may be of therapeutic benefit (55). …”
Section: Discussionmentioning
confidence: 87%
“…The protection afforded by fiber and resistant starch in experimental colitis are thought to be dependent on SCFA production (Ito et al, 2009; Morita et al, 2004; Videla et al, 2001), and administration of exogenous butyrate promotes resistance to experimental colitis (Cresci et al, 2013; Leonel et al, 2013). Studies investigating dysbiosis in inflammatory bowel disease identified reduced abundance of butyrate-producing organisms (e.g., certain Roseburia and Faecalibacterium genera) and lower concentrations of butyrate associated with disease (Machiels et al, 2013; Eeckhaut et al, 2013; Sokol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial dysbiosis observed in many metabolic diseases can alter SCFA production and crossfeeding rates, leading to changes in colonic SCFA concentrations and ratios. Tributyrin, a butyrate produg, has been shown to reduce mucosal damage and intestinal permeability in experimental colitis (29). In addition, tributyrin has been shown to attenuate obesity-associated inflammation and insulin resistance (52).…”
Section: G906mentioning
confidence: 99%